2017
DOI: 10.1007/s11524-016-0111-4
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset of Sexual Intercourse and Parental Incarceration among African American Youth Living in Urban Public Housing

Abstract: Mass incarceration, substance use, and adolescent early onset of sex (e.g

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Consequently, with multiple minority identities, it is crucial for ESMY to develop a healthy relationship with each of their identities, especially because positive identity exploration is beneficial for development and linked with improved self-esteem (Crawford et al, 2002; Peplau & Fingerhut, 2007). In addition, strong self-esteem contributes to increased self-efficacy (Anderson, 1998), which is related to healthier sexual and physical behaviors (Nebbitt, Lombe, Sanders-Phillips, & Stokes, 2010) and less depressive symptomology (Humensky et al, 2010). Thus, Strengths First, a strength-based case management prevention intervention, was designed for ESMY, which incorporates individualized care plans to assist ESMY with life difficulties.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, with multiple minority identities, it is crucial for ESMY to develop a healthy relationship with each of their identities, especially because positive identity exploration is beneficial for development and linked with improved self-esteem (Crawford et al, 2002; Peplau & Fingerhut, 2007). In addition, strong self-esteem contributes to increased self-efficacy (Anderson, 1998), which is related to healthier sexual and physical behaviors (Nebbitt, Lombe, Sanders-Phillips, & Stokes, 2010) and less depressive symptomology (Humensky et al, 2010). Thus, Strengths First, a strength-based case management prevention intervention, was designed for ESMY, which incorporates individualized care plans to assist ESMY with life difficulties.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the four studies appraised as moderate all found a significant association between witnessing FV and increased sexual risk-taking behavior. Five studies, all of weak quality, did not find any significant association between witnessing FV and sexual risk-taking behavior (Nebbitt et al, 2010; Steinberg et al, 2006; Toomey & Nelson, 2001; D. R. Voisin et al, 2014; Yi et al, 2010).…”
Section: Resultsmentioning
confidence: 87%
“…A total of 14 studies investigated at least one outcome related to sexual risk-taking behavior (see Table 4). None was appraised as being of strong quality; 4 were of moderate quality (Annerback, Sahlqvist, Svedin, Wingren, & Gustafsson, 2012; Bellis et al, 2014; Hillis et al, 2001; Lyerly & Brunner Huber, 2013); the remaining 10 were of weak or very weak quality (Elliott et al, 2002; Lepisto, Luukkaala, & Paavilainen, 2011; Nebbitt, Lombe, Sanders-Phillips, & Stokes, 2010; Orgiles, Carratala, & Espada, 2015; Steinberg, Davila, & Fincham, 2006; Toomey & Nelson, 2001; Tschann et al, 2002; Dexter R. Voisin, 2005; D. R. Voisin et al, 2014; Yi et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between neighborhood poverty or socioeconomic status and mental health is well‐established (Kessler et al., ; Leventhal & Brooks‐Gunn, ; Leventhal, Dupere, & Brooks‐Gunn, ; Sampson, Morenoff, & Gannon‐Rowley, ). Research suggests that specific aspects of the neighborhood environment, such as physical and social disorder, low collective efficacy, and exposure to violence, may have a negative effect on adolescent mental health and increase engagement in risky behaviors (Aneshensel & Sucoff, ; Gorman‐Smith, Tolan, & Henry, ; Lang et al., ; Nebbitt, Lombe, Sanders‐Phillips, & Stokes, ; Overstreet, ; Voisin, Jenkins, & Takahashi, ). Protective aspects of neighborhoods are also important, including neighborhood support and collective efficacy, which are associated with lower levels of individual adolescent problem behaviors, including conduct problems, substance use, and risky sexual behavior (Brody et al., ; Widome, Sieving, Harpin, & Hearst, ).…”
Section: Introductionmentioning
confidence: 99%